Properties of the Z(3) Interface in (2+1)-D SU(3) Gauge Theory - West, S; Wheater, J (1995)
A study is made of some properties of this interface in the SU(3) pure gauge theory in 2+1 dimensions. At high temperatures, the interface tension is measured and shows agreement with the perturbative prediction. Near the critical temperature, the behaviour of the interface is examined, and its fluctuations compared to a scalar field theory model.